Pathogens causing septic complications in patients of the Liver Transplantation Unit in a multidisciplinary hospital - T. V. Chernenkaya; N. V. Evdokimova; O. D. Olisov; M. S. Novruzbekov (Трансплантология (Москва))
Background. Despite the advances achieved in transplantation, the problem of septic infection in this field still remains crucial. This can largely be attributed to the immunocompromised status of patients, and the constant growth in the number of resistant strains of pathogens causing septic infection.The objective of the study was to identify the spectrum of septic infection pathogens and their antibiotic sensitivity in patients of the Liver Transplantation Department of the N.V. Sklifosovsky Research Institute for Emergency Medicine.Material and methods. The microbiology study results of 2,324 samples obtained from 236 patients who had been treated from 01.01.2023 to 30.06.2024 were analyzed. A total of 879 strains of microorganisms were isolated. In cases when carbapenem-resistant strains were isolated from the blood of patients, the carbapenemase genes were identified using an immunochromatography method.Results. Among pathogens, Gram–negative rods accounted for 54% of the total number of strains, Gram–positive bacteria accounted for 43%, yeasts of Candida spp. made 3%. Enterobacterales dominated among Gram-negative bacteria. Klebsiella pneumoniae strains were the absolute leader (33.0% of the total number of strains). Non-fermenting rods accounted for 11.3% of the isolated strains. Among the Gram-negative pathogens, the prevailing ones were the strains multidrug-resistant to the main classes of antibacterial drugs used in medical practice. Of all K. pneumoniae strains, the percentage of strains resistant to amikacin, ciprofloxacin, imipenem, and meropenem made 72.4%, 95.5%, 89.3%, and 87.9% respectively. Coagulase-negative staphylococci (18%) and enterococci (19.5%) prevailed among the Gram-positive cocci flora. Vancomycin, linezolid, and daptomycin retained antistaphylococcal effect. In carbapenemresistant K. pneumoniae and E. coli strains isolated from patients' blood, the NDM metallo-beta-lactamases and serine carbapenemases of the OXA-48 group prevailed.Conclusion. The prevailing pathogens that cause septic infection in patients with surgical diseases of the hepatobiliary zone include K. pneumoniae strains among the Gram-negative microflora, and coagulase-negative staphylococci and enterococci among Gram-positive ones. The study results have confirmed the global trend towards an increase in the number of resistant strains among the pathogens of septic infections.